Sequence stratigraphic architecture and facies analysis of the Oligocene Barail Formation, Surma basin, Bangladesh: implications for depositional dynamics and basin evolution - Md. Abdur Rahman,; Md. Shafiqul Alam, (International Journal of Advanced Geosciences, 2024)
This study systematically explores the sequence stratigraphy and depositional history of the exposed Oligocene Barail Formation within the Surma Basin, northeastern Bangladesh, an area recognized for its petroleum potential. Using integrated field observations, sedimentological analysis, and sequence stratigraphy, the research examines the influence of tectonics, climate, and eustatic sea-level fluctuations on sedimentary architecture. A total of ten lithofacies were identified and grouped into three facies associations, indicating fluvial to tide-dominated braided channel systems. The Barail Formation is categorized within Megasequence 2 (MS-2), characterized by a regressive erosional surface (RES) at its base and a transgressive erosional surface (TES) at its top, indicating a shift from progradational to retrogradational stacking patterns. Increased terrigenous sedimentation between 38 to 21 million years ago is attributed to regional tectonic uplift and climate change. The analysis revealed six parasequence sets corresponding to distinct systems tracts: PS1 (lowstand) shows regressive sedimentation, PS2 and PS3 (transgressive) exhibit retrogradational stacking, while PS4 and PS5 (highstand) demonstrate progradational stacking patterns. PS6 represents a regressive phase marked by lateritic conglomerates. These insights enhance the understanding of the Barail Formation’s depositional environments and contribute to refining sequence stratigraphic models critical for foreland basin hydrocarbon exploration.